PERBANDINGAN METODE CERTAINTY FACTOR DAN DEMPSTER SHAFER DALAM MENDIAGNOSIS PENYAKIT DIABETES MELLITUS PADA RUMAH SAKIT UMUM DAERAH KOTA KENDARI - Wasda Bil Husna; Herdi Budiman; La Surimi (Program Studi Ilmu Komputer FMIPA-UHO, 2025)
Diabetes Mellitus is a chronic disease that requires early and accurate diagnosis. This study aims to develop an expert system to diagnose Type 2 Diabetes Mellitus by comparing Certainty Factor and Dempster-Shafer methods. The system was developed using rule-based reasoning with symptom data and expert confidence values. Evaluation using a confusion matrix shows that the Certainty Factor method achieved higher accuracy than the Dempster-Shafer method.